2010
DOI: 10.1179/174329408x326399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiAlN PVD coatings on corrosion performance of WC–6%Co

Abstract: The present study has been carried out to evaluate the corrosion performance of three different (Ti12xAlx)N/TiN multilayers coatings commercially deposited on WC-Co inserts. Two of these coatings were nanostructured, and all of them presented different Ti/Al atomic ratios varying from 2 : 3 up to 7 : 3 and were deposited by employing a commercial physical vapour deposition cathodic arc process. X-ray diffraction analysis indicated that the grain size for both the TiAlN and TiN layers in the coatings architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Nitride hard compound coatings prepared by various physical vapour deposition (PVD) processes are found most frequently used in every demand. [1][2][3][4][5] Especially, high hardness, excellent wear and corrosion resistance enable high Al content AlTiN particularly to improve the durability of the coating. With respect to tribological properties, some papers have reported detailed research at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nitride hard compound coatings prepared by various physical vapour deposition (PVD) processes are found most frequently used in every demand. [1][2][3][4][5] Especially, high hardness, excellent wear and corrosion resistance enable high Al content AlTiN particularly to improve the durability of the coating. With respect to tribological properties, some papers have reported detailed research at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Numerous studies during the last two decades have shown that the cubic fcc-TiN structured coatings with high aluminium content (such as TiAlN or AlTiN) can provide better thermal stability (900uC) and wear protection than aluminium free nitride or carbide coatings (such as CrN, TiN and TiC). [16][17][18][19][20] Therefore, during the last few years, industrial application of monolayer and multilayer coatings based on TiAlN and deposited using PVD methods have considerably increased. 21 The addition of chromium (Cr) to (Ti, Al)N coating leads to further increase in thermal stability, mechanical strength, chemical inertness and hardness of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] There are different methods for producing CMMA coatings, e.g. physical vapour deposition, [9][10][11] chemical vapour deposition 12 and electrodeposition. 13 Electrolytically, such alloys can be obtained by either single bath technique (SBT), where deposition takes place in a plating solution containing ions of the alloy components, or double bath technique, where deposition is carried out from separate plating baths using a manual and automated transfer of the substrate from one bath to another.…”
Section: Introductionmentioning
confidence: 99%